ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI INDUSTRI KECIL DAN MENENGAH (IKM) TAHU BAKSO DI KECAMATAN UNGARAN, KABUPATEN SEMARANG - Farida Yuana Rahmawati; Agus Setiadi; Edy Prasetyo (Universitas Tidar, 2021)
This study was conducted to determine whether the use of production factors for the Small and Medium Industry (IKM) tofu meatballs was technically and economically efficient, the study also aimed to determine the level of technical efficiency and economic efficiency of the use of production factors for Small and Medium Industries (IKM). tofu meatballs located in Ungaran, Semarang, Central Java. The production factors analyzed include the amount of tofu used, the number of meatballs used, labor, gas, and packaging. The technique used in sampling is the saturated sample technique, which makes the entire population of 28 IKM owners into the sample. Data processing methods using Microsoft excel and SPSS 23. Data processing includes multiple linear regression test, t test, f test, technical efficiency analysis, and economic efficiency analysis. The results of this study are the production factors of tofu meatballs in the form of tofu, meatballs, labor, gas, and packaging are not yet economically efficient because the EE value is more/less than 1.Keywords: meatball tofu, production factors, technical efficiency, economic efficiency